2013
DOI: 10.1371/journal.pone.0054495
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Intake of Folate, B-Vitamins and Methionine and Breast Cancer Risk among Hispanic and Non-Hispanic White Women

Abstract: BackgroundLow dietary folate intake is associated with several neoplasias, but reports are inconsistent for breast cancer. Additionally, the association of folate with breast cancer estrogen receptor (ER) status is not well established.ObjectiveTo determine if dietary intakes of folate, B-vitamins (B2, B6, B12) and methionine are associated with breast cancer risk and ER status in Hispanic, and non-Hispanic White women in the southwestern US.Materials and MethodsPrimary breast cancer cases (n = 2,325) in the 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
24
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 68 publications
7
24
1
Order By: Relevance
“…It has been reported that high intake of folate is beneficial to women who are deficient in nutrient gain. Several previous studies have reported inconsistent results for folate intake and breast cancer risk (Ma et al, 2009;Wu et al, 2012;Tavani et al, 2012;Islam et al, 2013;Qin et al, 2013; Yang et al, 2013). In our study, we reported that folate intake does not play a protective role in breast cancer risk in Chinese population.…”
Section: Discussioncontrasting
confidence: 58%
“…It has been reported that high intake of folate is beneficial to women who are deficient in nutrient gain. Several previous studies have reported inconsistent results for folate intake and breast cancer risk (Ma et al, 2009;Wu et al, 2012;Tavani et al, 2012;Islam et al, 2013;Qin et al, 2013; Yang et al, 2013). In our study, we reported that folate intake does not play a protective role in breast cancer risk in Chinese population.…”
Section: Discussioncontrasting
confidence: 58%
“…Genetic variations in enzymes involved in one-carbon metabolism are good candidates for examining the impact of their effects and interactions on BC risk. Epidemiological evidence suggests that the risk of BC may be reduced by increasing the consumption of folate and related B vitamins (Zhang et al, 2011;Yang et al, 2013). In the present study, we investigated whether the TSER and TS 3'-UTR polymorphisms in the TS gene, a molecule that plays a key role in DNA synthesis, are associated with the risk of BC development.…”
Section: Discussionmentioning
confidence: 96%
“…Low dietary folate intake has been associated with risk of various cancers, such as colorectal cancer, pancreatic cancer, prostate cancer and gastric cancer (Bassett et al, 2013;Lin et al, 2013;Collin, 2013;Gao et al, 2013). Recently, several studies reported a protective effect of folate intake on breast cancer risk Yang et al, 2013;Islam et al, 2013). However, evidence from two recent studies have indicated an inverse association (Ericson et al, 2007;Maruti et al, 2009a), and some other studies have shown that the reduced risk only exists in certain populations, such as women with high levels of alcohol intake or premenopausal Chinese women (Levi et al, 2001;Shrubsole et al, 2011).…”
Section: Introductionmentioning
confidence: 99%